Crab bioturbation reduces carbon storage in salt marshes under more robust mechanisms than plant invasiveness - Hua, Yujie; Chen, Huayu; Ren, Linjing; Tang, Jianwu; Li, Xiuzhen (Frontiers in Marine Science, 2024)
Introduction The macrobenthos are crucial for the stability of estuarine ecosystems due to their burrowing behavior in the sediment and their uptake of nutrients from plants. These activities lead to significant alterations in both the morphological and biogeochemical processes within the region. Methods However, there is limited investigation into carbon cycling processes specifically related to crab bioturbation. Additionally, few studies have examined enzymatic activities and carbon fractions in sediments from crab burrow walls at different crab growth stages. This study aims to explore the impact of both plant invasiveness and crab bioturbation on carbon storage. Results Our findings suggest that plant invasion leads to higher organic accumulation due to the reduction of recalcitrant organic carbon (ROC) (decreased by 11.6% in invasive and 62.6% in native site from April to December), faster photosynthetic rates (25.8 μmol/m2 s in invasive and 10.7 μmol/m2 s in native site), and an increased presence of arbuscular mycorrhizal fungi (AMF) in the soil over time. However, the increase of easy oxidized carbon (EOC) may lead to less carbon storage in soil (increase by 67.7% in invasive and 48.8% in native site from April to December). In addition to invasiveness, the bioturbation activities of macrobenthos also affect carbon storage. Sediments from crab burrows exhibit higher EOC content (33.6% more than the bulk soil) and higher levels of carbon cycling-related enzymes, including S-ACT, S-β-GC, and S-ACP activities (24.2%, 8.99%, and 135.6% higher than the bulk soil, respectively). Discussion These changes contribute to reduced carbon accumulation in the soil. Therefore, crab bioturbation is a more significant factor affecting carbon sink capacity than plant invasion.